כיסוי וגילוי: ניסיון להתחקות אחר סוד גילוי העריות ולאתר את עקבותיו או את אופני הסגרתו ביצירות פרי עטן של רות אלמוג בסיפורה ״מרתה תמתי עד נצח״, איריס לעאל בספרה ״אושר פתאומי״ ולאה איני בספרה ״סדומאל״ - שירב פנינה (מכאן, 2010)
The paper “Concealment and Exposure” discusses three stories written by the Israeli women-writers Ruth Almog, Iris Leal and Lea Eini, at the center of which lurks a dark secret of father-daughter incest. Almog’s story was published in 1986, whereas the other two were published more than ten years later. An incest story, by its very definition, is surrounded by various censoring circles: The suppression and shame of the victim herself, the family who often keeps the secret from being publicly exposed, the immediate social environment and sometimes the therapeutic and the juridical circles. The three stories reflect very different narrative and representational techniques of dealing with the trauma and its verbalization. Almog’s story can be characterized by the vagueness and ambiguousness of its narrative voice, leaving open the question, did it or didn’t it actually happen, and calling for psychoanalytical reading methods to uncover the suppressed. The latter two stories are both rather blatant: It did, no doubt, take place. Despite this difference, all stories embody the victim’s impossibility to retrieve the traumatic memory in a coherent narrative.